2018
DOI: 10.1039/c8an00688a
|View full text |Cite
|
Sign up to set email alerts
|

Detection of exogenous substances in latent fingermarks by silver-assisted LDI imaging MS: perspectives in forensic sciences

Abstract: For over one hundred years, the fingerprint has reigned as one of the most trusted pieces of forensic evidence for suspect identification. In the last few decades, the modernization of chemical analysis technologies led scientists to explore new possibilities to further analyse fingermarks sampled from a crime scene. Indeed, the detection of chemicals a suspect has been in contact with before or during the crime can provide valuable insights into criminal investigations. In this regard, imaging mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 59 publications
0
19
0
1
Order By: Relevance
“…Procaine Kaplan-Sandquist, LeBeau, and Miller (2014), Kaplan-Sandquist, LeBeau, and Miller (2015) Quetiapine (antipsychotic drug) Costa, Frampas, et al (2019), Sympathomimetics: methylephedrine [ephedrine], pseudoephedrine Kaplan-Sandquist et al (2014), Kuwayama et al (2014), Kaplan-Sandquist et al (2015), Fowble and Musah (2019) Terbinafine (antifungal drug) Lim and Seviour (2012) 9-Tetrahydrocannabinol (THC) [11-nor-9-carboxy-Δ 9tetrahydrocannabinol, tetrahydrocannabinolic acid] Hazarika et al (2008), Ifa, Manicke, Dill, and Cooks (2008), Groeneveld et al (2015), Lauzon and Chaurand (2018), Hudson et al (2019) Verapamil Yagnik, Korte, and Lee (2013) The examples given above are only some of the materials that may be found and providing an exhaustive list is not possible here. Blood is probably the most significant contaminant that may be encountered in a fingermark at a crime scene.…”
Section: Drugs [Metabolites] Referencesmentioning
confidence: 99%
“…Procaine Kaplan-Sandquist, LeBeau, and Miller (2014), Kaplan-Sandquist, LeBeau, and Miller (2015) Quetiapine (antipsychotic drug) Costa, Frampas, et al (2019), Sympathomimetics: methylephedrine [ephedrine], pseudoephedrine Kaplan-Sandquist et al (2014), Kuwayama et al (2014), Kaplan-Sandquist et al (2015), Fowble and Musah (2019) Terbinafine (antifungal drug) Lim and Seviour (2012) 9-Tetrahydrocannabinol (THC) [11-nor-9-carboxy-Δ 9tetrahydrocannabinol, tetrahydrocannabinolic acid] Hazarika et al (2008), Ifa, Manicke, Dill, and Cooks (2008), Groeneveld et al (2015), Lauzon and Chaurand (2018), Hudson et al (2019) Verapamil Yagnik, Korte, and Lee (2013) The examples given above are only some of the materials that may be found and providing an exhaustive list is not possible here. Blood is probably the most significant contaminant that may be encountered in a fingermark at a crime scene.…”
Section: Drugs [Metabolites] Referencesmentioning
confidence: 99%
“…However, fingerprinting has remained at large unchanged and unchallenged in terms of workflow, scope and visualisation techniques. But despite successful, there is a number of scenarios, in which the process of matching a crime scene mark to a fingerprint record fails, for example because the mark is smudged, partial, empty, overlapped or beyond the Always employed for direct biometric identification exploiting the ridge pattern characteristics, the chemical composition of a mark can indeed additionally reveal personal information about its owner which can be used to support an investigation; it may be particularly useful when the ridge detail is insufficient or the mark composition can be linked to a better physical quality mark of the same owner at the crime scene, thus helping with the crime scene dynamics reconstruction 3 . Through detecting substances that are normally produced by our body and present in sweat, and therefore in fingermarks, so called endogenous, those that have entered the body and have been excreted through sweat (semiendogenous), for example through medications, drugs etc., and those that come in contact with our fingertips (exogenous) we can potentially undertake a sort of criminal profiling 4 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Research has also shown that exogenous compounds in ngerprints can be used to connect an individual to a certain lifestyle or illicit activity. [8][9][10][11] Mass spectrometry imaging (MSI) provides the advantage of simultaneous collection of both chemical and spatial information, making it popular for the analysis of latent ngerprints because an image that could be used for a database search is generated while additional chemical information is being obtained. As a surface technique, MSI requires very little sample preparation.…”
Section: Introductionmentioning
confidence: 99%